Study the Effect of Some Heterocyclic Compounds on the Cholinesterase Enzyme in Human Blood Serum - Meaaad Nasser (Journal of Global Pharma Technology, 2019)
This research involve synthesis of three type of heterocyclic derivatives (thiadiazole, thiadiazole-shiff base, thiadiazole-azo) by three step, the first step react p-hydroxybenzoic acid with thiosemicarbazide to get compound (1), the second step include react (1) with (p-chloro benzaldehyde, p-hydroxy benzaldehyde) to get thiadiazole-shiff base derivatives (2,3) respectively, in other side the third step involve react (1) with 1-naphthol and salicylaldehyde to get, thiadiazole-azo derivatives (4,5) respectively, all these derivatives were characterize by FT-IR, 1H-NMR, 13C-NMR spectra .After that the effect of these compounds was studied on the activity of the enzyme acetyl cholinesterase in the human serum. Compounds that have the donated groups in the ring showed a high inhibition ratio, either the compounds containing the withdrawing groups in the ring showed a low inhibition ratio because the effect of resonance.Keywords: Thiadiazole, thiadiazole-shiff base, thiadiazole-azo, cholinesterase